(untitled) (Progressive Agriculture, 2016)
The quality of wheat seed samples of 11 varieties viz. Akbar, Kanchan, Barkat, Sonalika , Paban, Prodip, Satapdi, BARI gom 25, BARI gom 26, BARI gom 27 and BARI gom 28 from 7 different Upazillas of Bogra and 5 different Upazillas of Naogaon were tested and categorized into six components viz. Grade-0 (72 to 86.7%), Grade-1 (2.9 to 7.5%), Grade-2 (2.1 to 6.0%), Grade-3 (1.7 to 4.5%), Grade-4 (2.4 to 8.4%) and Grade-5 (1.5 to 7.6%). The highest percentage of Grade-0 seeds (86.7%) was recorded in wheat variety of BARI gom 28 and the lowest percentage of Grade-0 seeds (72%) was recorded in variety Kanchan. The moisture content of the seed samples ranged from 10.22 to 13.81%, where the highest percentage of moisture content was found in wheat variety of Kanchan and the lowest in wheat variety of BARI gom 28. The 1000-seed weight ranged from 40.00 to 42.85 g where significantly highest weight was recorded in wheat variety of Sonalika followed by BARI gom 27 and the lowest in BARI gom 28. Health test by Blotter method resulted eight different seed borne fungi belonging to six genera viz. Bipolaris sorokiniana (0.5 to 30.5%), Alternaria tenuis (0.5 to 25%), Fusarium moniliforme (0.0 to 33.5%), Fusarium oxysporum (2.7 to 53%), Curvularia lunata (0.0 to 5.5%), Aspergillus niger (0.0 to 18.5%) and Penicillium spp. (0.0 to 1.5%). Out of 11 samples tested germination of seeds ranged from 98.0 to 73.5%. Wheat seeds of variety Kanchan was treated with plant extracts, BAU-Biofungicide and chemical fungicides (Bavistin, Tilt and Provex) while the highest (11%) incidence of Bipolaris sorokiniana was recorded in untreated control and the lowest (0.0%) in seed treatment with BAU-Biofungicide followed by seed treatment with Provax and Tilt. Seed germination ranged from 56.0 to 98.0% where the highest (98.0%) and lowest (56.0%) germination was recorded in case of seed treatment with BAU-Biofungicide and Tilt. BAU-Biofungicide increased 41.75% vigor index over untreated control. Progressive Agriculture 27 (2): 101-109, 2016